Dual‐Color Photoconvertible Fluorescent Probes Based on Directed Photooxidation Induced Conversion for Bioimaging. Issue 4 (14th December 2022) - Saladin, Lazare; Breton, Victor; Dal Pra, Ophélie; Klymchenko, Andrey S.; Danglot, Lydia; Didier, Pascal; Collot, Mayeul
Abstract: We herein present a new concept to produce dual‐color photoconvertible probes based on a mechanism called Directed Photooxidation Induced Conversion (DPIC). As a support of this mechanism, styryl‐coumarins (SCs ) bearing Aromatic Singlet Oxygen Reactive Moieties (ASORMs) like furan and pyrrole have been synthesized. SCs are bright fluorophores, which undergo a hypsochromic conversion upon visible light irradiation due to directed photooxidation of the ASORM that leads to the disruption of conjugation. SC‐P, a yellow emitting probe bearing a pyrrole moiety, converts to a stable blue emitting coumarin with a 68 nm shift allowing the photoconversion and tracking of lipid droplet in live cells. This new approach might pave the way to a new generation of photoconvertible dyes for advanced bioimaging applications. Abstract : A method to obtain bright dual‐color photoconvertible fluorophores is presented based on a new mechanism called Directed Photooxidation Induced Conversion (DPIC). The mechanism is based on the directed oxidation of the pyrrole that is conjugated to the fluorophore. This approach led to SC‐P, which stains the lipid droplets in live cells and that undergoes a hypsochromic shift of 68 nm upon visible light irradiation.